2010
DOI: 10.1177/0022034510375827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regular and Low-fluoride Dentifrices on Plaque Fluoride

Abstract: Previous studies have indicated that the use of low-fluoride dentifrices could lead to proportionally higher plaque fluoride levels when compared with conventional dentifrices. This double-blind, randomized, crossover study determined the effects of placebo, low-fluoride, and conventional dentifrices on plaque fluoride concentrations ([F]) in children living in communities with 0.04, 0.72, and 3.36 ppm F in the drinking water. Children used the toothpastes twice daily, for 1 wk. Samples were collected 1 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
3
14
0
2
Order By: Relevance
“…However, in the study carried out in 2010, 24 the authors found that the fluoride concentrations in saliva and in dental biofilm remained elevated at 12 h after the last use of a fluoride dentifrice. A possible explanation for these contradictory results could be the different fluoride concentrations in the water supply of the city where the studies were conducted.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, in the study carried out in 2010, 24 the authors found that the fluoride concentrations in saliva and in dental biofilm remained elevated at 12 h after the last use of a fluoride dentifrice. A possible explanation for these contradictory results could be the different fluoride concentrations in the water supply of the city where the studies were conducted.…”
Section: Discussionmentioning
confidence: 96%
“…30 However, two studies carried out by the same authors and conducted in an area with a fluoridated water supply yielded contradictory results. 22,24 The results of the study conducted in 2006…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the normally distributed data (plaque mass, salivary flow) the data are presented as mean and standard error. However, the fluoride data, with the exception of the salivary particulate concentrations, required logarithmic transformation [Zero et al, 1992a;Vogel et al, 2006aVogel et al, , b, 2008aPessan, 2010] in order to satisfy the requirement of variance homogenicity or normality required for the use of parametric tests. Consistent with the log transformation, the fluoride data are presented as the geometric mean, i.e.…”
Section: Statistical Analysis and Data Presentationmentioning
confidence: 99%
“…Regarding the use of these dentifrices in areas with higher fluoride concentrations, it could be expected from the data regarding plaque fluoride uptake that no differences in caries progression rates would be found among the tested dentifrices. This is due to the fact that the high fluoride concentrations present in the drinking water would make the differences among the fluoride concentrations and pH of the dentifrices less important [Pessan et al, 2008[Pessan et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%